Особливості анатомічної будови однорічних здерев’янілих пагонів Calycanthus floridus L. - Gavrylyuk, O.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
Anatomical structure of lignified shoots of Calycanthus floridus L. was studied. The main features of shoot structure in the conditions of Volyn Polissya are defined. An analysis of anatomic topography, cross- and longitudinal sections of C. floridus lignified shoots show structural features of the primary and secondary cortex. It is proved that the content of essential oils in secretory cells of parenhymatous tissues influence formation of callus in C. floridus cuttings. Found dependence is one of the causes of poor rooting of cuttings.